2015
DOI: 10.1038/mi.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing TNFα restores glucocorticoid sensitivity in a mouse model of neutrophilic airway inflammation

Abstract: Asthma is a heterogeneous disorder, evidenced by distinct types of inflammation resulting in different responsiveness to therapy with glucocorticoids (GCs). Tumor necrosis factor α (TNFα) is involved in asthma pathogenesis, but anti-TNFα therapies have not proven broadly effective. The effects of anti-TNFα treatment on steroid resistance have never been assessed. We investigated the role of TNFα blockade using etanercept in the responsiveness to GCs in two ovalbumin-based mouse models of airway hyperinflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 59 publications
2
51
0
Order By: Relevance
“…A key role for the inflammatory cytokine TNFα was also recently demonstrated in a model of steroid-resistant neutrophilic airway inflammation induced by sensitization with complete Freund's adjuvant (CFA), where inhibition of TNFα could restore steroid sensitivity. 40 These findings provide support for key roles of innate immune inflammation in the development of steroid resistance.…”
Section: Steroid Resistancementioning
confidence: 66%
“…A key role for the inflammatory cytokine TNFα was also recently demonstrated in a model of steroid-resistant neutrophilic airway inflammation induced by sensitization with complete Freund's adjuvant (CFA), where inhibition of TNFα could restore steroid sensitivity. 40 These findings provide support for key roles of innate immune inflammation in the development of steroid resistance.…”
Section: Steroid Resistancementioning
confidence: 66%
“…81 In an experimental model of Th1/neutrophil-predominant asthma, TNFa reduced the responsiveness to steroids and neutralization of TNFa using etanercept restored glucocorticoid sensitivity. 82 Recently, the TNF superfamily member, LIGHT, has been implicated as a mediator in asthmatic airway inflammation. Human bronchial epithelial cells express the receptor for LIGHT, the lymphotoxin b receptor (LTbR) and upon stimulation with LIGHT release IL-6, oncostatin M, MCP-1, growth-regulated protein a and IL-8.…”
Section: Neutrophilic Inflammationmentioning
confidence: 99%
“…In contrast, mice sensitized with aluminum hydroxide (Alum) display a conventional Th2/eosinophil-driven inflammation that responds well to GCs [126]. Recently, we found that neutralization of TNF, using etanercept, restores GC sensitivity in the GC-resistant OVA-CFA model [127]. Furthermore, cytokine inhibition was found to restore GC sensitivity also in GCR patients, as the IL-1 receptor antagonist anakinra was found to be revert GC sensitivity in patients with corticosteroid-resistant autoimmune inner ear disease [128].…”
Section: Gc Resistancementioning
confidence: 83%